Message framing and counseling of parents on children's physical activity – an experimental study. Issue 1 (1st January 2018) - Drouin, Olivier; Young, Meredith; King, Nicholas
ABSTRACT: How messages are framed (gain or loss frame) modulate the effect of health information on physical activity level in adults. The role of framing of health information messages to parents about their child's physical activity is unknown. Adult participants (parents) were randomized to see a video that either emphasized the benefits of physical activity (gain frame) or the risks of physical inactivity (loss frame) in children. The primary outcome was the change in the reported level of physical activity for their children between baseline and two-week follow-up. 92 individuals participated in the study and we obtained follow-up data for 48 participants (20 gain frame and 28 loss frame). Using a generalized linear model, we found that the frame presented to parents significantly influenced the trajectory of their child's physical activity ( p = 0.03), with the loss frame condition resulting in more favorable trajectory. Both the willingness to pay for organized physical activities and the perceived barriers to physical activity were similar between the two intervention groups. The change in the reported level of activity of the child over a two-week period was significantly different whether parents were exposed to a loss frame or a gain frame video message.